Influence of organizational culture on company performance - Mohd Yusuff, Rosnah; Abdul Rashid, Ahmad Busu; Zulkifli, Norzima (2008)
The lack of organizational effort to access cultural compatibility or fit prior to the engagement of firms has contributed to the failure of several mergers and acquisition. A Korean public listed company with manufacturing plants in Malaysia and New Zealand found that the performances of the newly acquired plants were significantly lower than the manufacturing plants in Korea. In this study, the influence of national culture on organizational culture and the effect on the organizational performance was conducted on 6 manufacturing plants in Korea (2), Malaysia (3) and New Zealand (1). Hofstede's culture dimensions were used to determine culture diversity between the manufacturing plants. The values survey module was used to calculate the index scores on five dimensions of national value system as components of national cultures:power distance, individualism, masculinity, uncertainty avoidance and long term orientation. The model of culture fit assesses the dimension of socio-cultural environment, internal work culture and HRM practices. The resulting multiple regression analysis showed that there are cultural diversities between the manufacturing plants and national culture does influence organizational performance. The result also showed that a dimension of internal work culture does influence organizational performance.